RUMAH SAKIT ORTOPEDI DI SEMARANG DENGAN PENDEKATAN FISIOTERAPI - Ajeng Hardanti Mulia Putri; Marsudi Marsudi; Ahmad Farkhan (ARSITEKTURA, 2014)
Abstract: Designing Orthopaedic Hospital in Semarang background by the number of people with orthopedic cases in Semarang, yet the presence of Orthopaedic Hospital, as well as the special needs of health care facilities bones, so that the fulfillment of the needs of all activities of the user space are issues that can be raised of how to design a Hospital Orthopedic services that serves as the healing process both physically and non-physically special orthopedic patients on the medical action with infrastructure and facilities accessible to patients in accordance with both physical and psychological characteristics of the patient. In the healing process of patients hospitalized with psychiatric therapy is an effective method for healing physical and psychological character of the patient, so that the approach to the design of a generating Physiotherapy Orthopaedic Hospital design that creates a comfortable atmosphere in the space and facilities needed menyadiakan according to the characteristics of the users home pain and buildings can assist in the healing process of patients both physically and psychologically and reflect the activities in it. Keywords: Orthopaedic Hospital, Orthopaedic, Physiotherapy